The Effect of Mathematic-English on Students’ Tenses Mastery in Differentiated Instruction - Fatmawati, Siti Zuliana; Candraloka, Olyvia Revalita (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Mathematic-English is a combination of Mathematics and English. it is the use of basic mathematical concepts and patterns of understanding English tenses. This study aimed to find out the effectiveness of Mathematic-English on students’ tenses mastery in Differentiated Instruction. This study employed the true experimental design featuring a pretest-posttest control group design. The research population was eleventh-grade students at SMA N 1 Tahunan. The research sample consisted of class XI-2 and XI-3, with XI-2 assigned as the control group and XI-3 as the experimental group. It has been selected through simple random sampling. The finding showed that there were significant differences in the mean scores before and after the test for both groups. In terms of the scores, there is a difference of 10.06 in the control group, whereas the experimental group exhibits a difference of 22.18. In addition, the analysis results using the independent sample t-test indicated that the t-test score was bigger compared to the t-table score (10.534>1.668). It indicates that the alternative hypothesis was accepted. Referring to the findings of the study, it can be concluded that the Mathematic-English model can improve students’ tense mastery.